2016
DOI: 10.1038/srep37550
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of lung volumes using body plethysmography and helium dilution methods in COPD patients: a correlation and diagnosis analysis

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic airway disease characterized by persistent airflow limitation. Moreover, lung hyperinflation evaluated by lung volumes is also the key pathophysiologic process during COPD progression. Nevertheless, there is still no preferred method to evaluate lung volumes. For this study, we recruited 170 patients with stable COPD to assess lung volumes stratified by airflow limitation severity. Lung volumes including residual volume (RV) and total lung capacity (TLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
(42 reference statements)
1
13
0
2
Order By: Relevance
“…Computed tomography may be affected by postural lung volume changes [ 28 ] and incomplete inspiration while Helium dilution may result in underestimation due to gas trapping [ 29 ]. Interestingly, gas trapping independently predicts patients with a larger difference of plethysmography and computed tomography derived total lung capacity [ 30 ] and inter-modal differences even were postulated as a diagnostic tool differentiating COPD severity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography may be affected by postural lung volume changes [ 28 ] and incomplete inspiration while Helium dilution may result in underestimation due to gas trapping [ 29 ]. Interestingly, gas trapping independently predicts patients with a larger difference of plethysmography and computed tomography derived total lung capacity [ 30 ] and inter-modal differences even were postulated as a diagnostic tool differentiating COPD severity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies which included restrictive patients and healthy subjects had reported a concordance up to 0.81. 21,27 Among subjects with COPD, we found poor agreement (CCC=0.60) between BP and cabin-less plethysmography, with an underestimation of TLC by cabin-less plethysmography. Despite this, in the lung bullae group, which was challenging because of the presence of unventilated air spaces, agreement between BP and cabin-less plethysmography was better (CCC=0.85), demonstrating a reasonable measurement of intrathoracic gas, but one that is affected by airflow obstruction.…”
Section: Discussionmentioning
confidence: 79%
“…[28][29][30][31][32] The agreement between BP and DLCO sb was poor in the presence of lung bullae and airflow obstruction (CCC=0.47 and CCC=0.18, respectively), consistent with other studies, finding that gas dilution method by a single breath, only measures correctly well ventilated lung volume. 19,27,[33][34][35][36][37] In a previous study including measurement of lung volumes with different methods 34 , a systematic overestimation of TLC with BP was observed, when All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the diagnosis of static hyperinflation requires the demonstration that FRC, determined by plethysmography, is greater than its upper limit of normal (ULN) 7 . Its evaluation by dilution procedures is not recommended as they underestimate the lung volumes proportionally to the severity of the airflow limitation 8 . Due to the inverse relationship between body mass and FRC in patients with COPD, its evaluation is also not recommended with reference equations that include weight or body surface area 9,10 .…”
Section: Definitions and Evaluation Proceduresmentioning
confidence: 99%